Modeling the morphological response of gravel–bed rivers subject to repeated sediment bypass tunnel operations - Facchini, Matteo; Vetsch, David F.; Boes, Robert M.; Siviglia, Annunziato (Frontiers in Earth Science, 2024)
Sediment Bypass Tunnels (SBTs) are operated during floods to re-establish sediment continuity past dams with the ultimate goal of decreasing accumulation in reservoirs. Depending on the location of the intake structure and operational conditions, SBTs may release either bedload-laden or bedload-free flows in form of sudden floods (pulses). When evaluating the impacts of SBTs, the traditional approach has been to monitor channel changes in the years following project completion. However, by the time these impacts become evident, mitigation is challenging. This research adopts a forward-thinking methodology, emphasizing the prediction of potential impacts during the project's early planning stages. We use a one-dimensional morphodynamic model to forecast the potential morphological response of a gravel-bed river with an idealized geometry to a series of SBT operations characteristic of projects in the Swiss Alps. The morphological response of the downstream reach over the medium to long term is influenced by the alternating pattern of bedload-laden and bedload-free flow releases. This pattern is instrumental in forming a transition region near the SBT outlet (hydrograph boundary layer (HBL)). Within the HBL, fluctuations in bed elevation and slope are localized, while variations in grain-size distribution persist throughout the downstream region. The way these releases alternate affects the long-term changes in the downstream reach. This can make them either match or differ from the slope and grain-size distribution seen upstream of the SBT.